Postoperative Free-Flap Monitoring Techniques - Kohlert, Scott; Quimby, Alexandra E.; Saman, Masoud; Ducic, Yadranko (Seminars in Plastic Surgery, 2019)
Free tissue transfer is commonly employed in the reconstruction of large or complicated defects. Postoperative flap failure from microvascular compromise is an uncommon but major potential complication of this procedure. As such, many postoperative monitoring techniques devices have been developed. This paper provides an overview of the wide variety of options available for surgeons today.
Keywords: free flap; postoperative monitoring; microvascular reconstruction